2017
DOI: 10.1038/nrg.2017.83
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of sexual conflict in the genomic era

Abstract: ABSTRACT:Sexual conflict occurs when selection acts in opposing directions on males and females. Case studies in both vertebrates and invertebrates indicate that sexual conflict maintains genetic diversity through balancing selection, which might explain why many populations show more genetic variation than expected. Recent population genomic approaches based on different measures of balancing selection have suggested that sexual conflict can arise over survival, not just reproductive fitness as previously tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
139
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(159 citation statements)
references
References 96 publications
8
139
1
Order By: Relevance
“…One hypothesis for this observation is that by chance Chromosome 2 carries an excess of loci with sex‐biased expression. This situation could result if there are many loci on that chromosome that experience SAS, which can lead to the evolution of sex‐biased expression (Cheng & Kirkpatrick, ; Grath & Parsch, ; Mank, ; Parsch & Ellegren, ). SAS acting on Chromosome 2 could also be the driving force for the fixation of the reciprocal translocation in Ammarnäs (discussed below).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis for this observation is that by chance Chromosome 2 carries an excess of loci with sex‐biased expression. This situation could result if there are many loci on that chromosome that experience SAS, which can lead to the evolution of sex‐biased expression (Cheng & Kirkpatrick, ; Grath & Parsch, ; Mank, ; Parsch & Ellegren, ). SAS acting on Chromosome 2 could also be the driving force for the fixation of the reciprocal translocation in Ammarnäs (discussed below).…”
Section: Discussionmentioning
confidence: 99%
“…If the selection pressures act in opposite directions in males and females, we refer to this as (inter‐) sexual conflict or sexual antagonism (Arnqvist & Rowe, ). Testing if sexual conflict maintains genetic variation in natural populations is a tremendous challenge—it requires both identifying loci that harbor sexually antagonistic alleles and determining whether those alleles are maintained as stable polymorphisms (Mank, ). Doing so genome‐wide is even harder because it is not tractable to identify sexually antagonistic alleles and test for stable polymorphisms at all loci.…”
mentioning
confidence: 99%
“…It has therefore been predicted that sexual conflict can maintain genetic variation in a manner similar to other forms of balancing selection (Kidwell et al., ; Owen, ). Indeed, a few large‐effect sexually antagonistic alleles have been identified that appear to be maintained as balanced polymorphisms (Mank, ).…”
mentioning
confidence: 99%
See 2 more Smart Citations